(untitled) (Scientific journal of the Fergana State University, 2023)
This article investigates the issue of interdisciplinary integration in the general education system. The concept of interdisciplinary integration is highlighted as a means of boosting and expanding students’ skills in independent thinking, perspective, knowledge acquisition, and, eventually, improving the entire educational process.